TRANSFORMASI PENDIDIKAN KARAKTER MELALUI KEBIJAKAN PEMERINTAH DI INDONESIA MENUJU GENERASI EMAS 2045 - Maisaroh, Anisa Amalia; Untari, Sri (Fakultas Politik Pemerintahan IPDN, 2024)
Abstract The current challenges of character building include moral and ethical crises due to technological advances, as well as gaps in values and labor market needs. The transformation of character education is important in realizing Indonesia's vision towards the Golden Generation 2045. This study aims to identify character education policies implemented by the Indonesian government, analyze the factors that influence the effectiveness of these policies, and analyze the roles of educational institutions, communities, and government in supporting the implementation of character education policies. The method used in this research is a literature review with five stages: finding literature relevant to the research topic, evaluating literature sources, identifying themes and gaps between theories, creating an outline structure in the preparation of literature, and preparing literature reviews that follow the standard format for writing academic papers. The results show that the character education policy is based on Law No 20 of 2003, Presidential Regulation No 87 of 2017, and Minister of Education, Culture and Research No 47 of 2023. Factors that influence the effectiveness of character education policies include the active involvement of various stakeholders such as teachers, parents, communities and businesses. This inter-stakeholder collaboration can improve policy support, implementation and monitoring, ensuring that each party plays an active role in creating an educational environment that supports students' character development. Educational institutions are responsible for integrating character learning in the curriculum, communities provide support and active participation, and the government makes supporting policies and provides financial support and infrastructure for the implementation of character education at all levels. Keywords: Transformation, policy, education, Indonesia.